2022
DOI: 10.1001/jamanetworkopen.2021.48794
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of HIV Preexposure Prophylaxis in Diverse, Real-World Settings

Abstract: Global HIV incidence remains high, with approximately 1.5 million new infections reported in 2020. 1 Preexposure prophylaxis (PrEP) consisting of oral tenofovir disoproxil fumarate and emtricitabine has been shown to be highly effective in preventing HIV infections. Oral daily PrEP (D-PrEP) is effective in preventing HIV among men who have sex with men (MSM), cisgender women, people who inject drugs, and transgender persons, whereas oral event-driven PrEP (ED-PrEP), taken around the time of sexual intercourse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Although provider education may seem like a solution to this issue, more than education may be needed as a recent enhanced provider training module did not significantly increase the number of participants prescribing HIV-PrEP [ 32 ]. A more thorough understanding of the types of training needed can help guide future efforts to improve PrEP uptake and delivery, such as tailored local educational resources and implementing system-level interventions such as trained navigators to support providers in PrEP discussions and initiation in diverse settings [ 33 , 34 ]. A recent systematic review of PrEP opportunities in US EDs showed the feasibility of counseling, scheduling, and referring patients for PrEP care [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although provider education may seem like a solution to this issue, more than education may be needed as a recent enhanced provider training module did not significantly increase the number of participants prescribing HIV-PrEP [ 32 ]. A more thorough understanding of the types of training needed can help guide future efforts to improve PrEP uptake and delivery, such as tailored local educational resources and implementing system-level interventions such as trained navigators to support providers in PrEP discussions and initiation in diverse settings [ 33 , 34 ]. A recent systematic review of PrEP opportunities in US EDs showed the feasibility of counseling, scheduling, and referring patients for PrEP care [ 35 ].…”
Section: Discussionmentioning
confidence: 99%